Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Dapat Meningkatkan Hasil Belajar Siswa dalam Menghitung Luas Segi Banyak di Kelas VI SDN. No. 028/XI Tanjung Tahun 2016/2017 - Nadirman Nadirman (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This study aims to improve the student’s learning outcomes in calculating the wide of many facets by applying cooperative learning model of group investigation type. The study involved 18 students of sixth class year 2016/2017 at SDN. No. 028/XI Tanjung, Hamparan Rawang Subdistrict, Sungai Penuh City, Jambi Province. This research is a Classroom Action Research that conducted in two cycles (Cycle I and Cycle II). Each cycle is done through two meetings with four activities namely planning, implementation, observation, and reflection. The research data was collected through observation and test. The data were processed by using descriptive analysis and simple statistical test. Application of cooperative learning model of group investigation type brought about changes in student learning activities. All students follow the learning with enthusiasm, follow all the learning stages in accordance with the rules, and can work together in groups. Most students have also been able to communicate the results of group work in front of the class and also have dared to submit feedback on the presentation of the results of other group discussions. The implementation of cooperative learning model of group investigation type also improves the learning outcomes of sixth grade students in SDN. No. 028/XI Tanjung year 2016/2017. Student’s learning outcomes seen from the mean and percentage of students who were able to fulfil the minimum criteria. Thus, cooperative learning model type group investigation can be an alternative to improve student learning outcomes in mathematics subjects, especially in calculating the wide of many facets.